Language usage of jargon and slang in strategic studies - Ong, Jessica Hai Liaw; Dani, Noor Aina; Johari, Ahmad Zaidi (American-Eurasian Network for Scientific Information, 2013)
The coherent view of language in strategic studies is to assemble a face out of a police identikit. All of the pieces, and no matter which ones, it does not look quite right. In this situation, it is necessary to specialize fairly rigidly and amidst the vast array of possible topics related to language, jargon and slang and this attracted the researchers. Methods: Language usage of jargon and slang is linked to strategic studies by the Speaking mnemonic. The Speaking Model offers a theoretical basis for language study that accounts for both linguistic variation from individual to individual and relative linguistic coherence across the social realm. Police jargon and slang is a unique language that police use to communicate with each other. It consists of terms, body language, acronyms, codes, and abbreviations. This can quickly and concisely be used to describe many things by the police both in written and verbal form. This language can describe people, places, property and situations by using The Speaking Model. This study is relevant to ascertain the perception of usage of jargon and slang by using The Speaking Model and this model can applied to study the elaborated codes of jargon and slang in sociolinguistic. Thus, the information obtained is jargon and slang associated in every profession but police jargon and slang is the most interesting one in strategic studies because of their own identity in communication. The Speaking Model is to look at a series of speech events and speech acts within a cultural context by using the first letters of terms for speech components and more vocabularies can be form. Shared knowledge of the linguistic code in police identity and as well as of the socio-cultural rules, norms gives values in a community.